PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. SEMESTA NUSTRA DISTRINDO CAB. PEKANBARU - Anuar, Saiful (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was conducted at PT. Semesta Nustra Distrindo Cab. Pekanbaru Pekanbaru Province..Does Organizational Culture Affect Employee Performance At PT. Semesta Nustra Distrindo Cab. Pekanbaru.? The purpose of this study was to determine the effect of Organizational Culture on Employee Performance at PT. Semesta Nustra Distrindo Cab. Pekanbaru. The research method used is descriptive and quantitative. The population in this study were employees of PT. Semesta Nustra Distrindo Cab. Pekanbaru, which amounted to 41 people, samples were taken from the entire population, so the number of samples was 41 people. Based on the equation of Simple Linear Regression Y = 16.144 + 0.467X. The constant is 16.144, meaning that if the independent value of the X variable (education and training) is 0, then the value of the assessment variable of Y (competence) is the same as 16.144. The value of t count > table (5.784 > 2.022) then Ho is rejected, meaning that there is a significant influence between education and training on competence. So it can be said that education and training affect competence. The total R Square (R2) is 0.462 or 46.2%. This shows that the proportion of contributions, the influence of independent variables (education and training) on the dependent variable (competence) is 46.2%. While the remaining 53.8% is influenced by other variables that are not included in this.